Comparison of Static and Dynamic Balance of Athletes of Different Sports in Conditions With and Without Posture Disturbances - Mostafa Shadkanlu Ostad; Ali Asghar Norasteh; Hamed Babagoltabar Samakoush (Islamic Azad University, Hamedan Branch, 2019)
Objective: Balance is a key component of motor skills to maintain posture and perform complex sports skills. The aim of this study was to compare the static and dynamic balance of athletes in different sports using different conditions of with/without postural perturbation. Methods: Participants were 42 athletes with 3 years of sports experience assigned into three groups of wrestlers (n=14), football players (n=14) and karate players (n=14). Static balance was assessed using the Balance Error Scoring System and dynamic balance measurement was done using the Star Excursion Balance Test. For measurement of postural perturbations or cognitive task, the countdown technique was used. Data were analyzed using Analysis of variance (ANOVA), Analysis of Covariance (ANCOVA), and paired t-test at a significance level of P≤0.05.  Results: There was no significant difference between the static and dynamic balance of athletes with postural perturbation in three groups. No significant difference was found between static balance with and without postural perturbation in three groups, but the difference was significant different between dynamic balance with and without postural perturbation, where their dynamic balance without postural perturbation was better.  Conclusion: Coaches and physiotherapists are recommended to use dual-task techniques in assessments.